The NAIMS cooperative pilot project: Design, implementation and future directions. (November 2018) - Oh, Jiwon; Bakshi, Rohit; Calabresi, Peter A; Crainiceanu, Ciprian; Henry, Roland G; Nair, Govind; Papinutto, Nico; Constable, R Todd; Reich, Daniel S; Pelletier, Daniel; Rooney, William; Schwartz, Daniel; et al.
The North American Imaging in Multiple Sclerosis (NAIMS) Cooperative represents a network of 27 academic centers focused on accelerating the pace of magnetic resonance imaging (MRI) research in multiple sclerosis (MS) through idea exchange and collaboration. Recently, NAIMS completed its first project evaluating the feasibility of implementation and reproducibility of quantitative MRI measures derived from scanning a single MS patient using a high-resolution 3T protocol at seven sites. The results showed the feasibility of utilizing advanced quantitative MRI measures in multicenter studies and demonstrated the importance of careful standardization of scanning protocols, central image processing, and strategies to account for inter-site variability.